Corrosion, oxidation, erosion and performance of Ag/W-based circuit breaker contacts: A review. (1st May 2018) - Kesim, M.T.; Yu, H.; Sun, Y.; Aindow, M.; Alpay, S.P.
Graphical abstract: Corrosion, oxidation and erosion behavior of Ag/W contacts are examined with a special emphasis on the materials properties. We limit ourselves to the effects of atmospheric corrosion and provide some examples for field and standard simulated laboratory tests that give insights into the long-term stability of contact materials. Abstract: Ag/W composite materials have been widely utilized as electrical contacts in low voltage circuit breakers. In this review, the corrosion, oxidation and erosion behavior of Ag/W contacts are examined with a special emphasis on the materials properties. For comparison, the oxidation/corrosion characteristics of the two main elemental constituents, Ag and W, are also reviewed. We limit ourselves to the effects of atmospheric corrosion and provide some examples for field and standard simulated laboratory tests that give insights into the long-term stability of contact materials. The effects of arcing and erosion on the performance of Ag/Refractory contacts are also discussed.